ECOEFICIENCIA EN LA UNIVERSIDAD HACIA UN DESARROLLO SOSTENIBLE - Bustamante Sánchez, Yolanda (2011)
Due to the environmental emergency that we are facing, it is necessary to implement eco efficiency measurements at university oriented to the rational use of resources, water, energy , generation of waste oriented to the sustainable development.